Stability analysis of Katarni rice (Oryza sativa) derived lines under different sowing dates - MAHTO, DIVYA; SINGH, P K; SATYENDRA,; PARVEEN, RABIYA; NAHAKPAM, SAREETA; KUMAR, MANKESH (The Indian Journal of Agricultural Sciences, 2023)
Katarni is a non-basmati traditional aromatic rice (Oryza sativa L.) cultivar of Bhagalpur district of Bihar. This rice is weak strawed, traditionally tall type, late maturing and easily prone to lodging. Due to photosensitive nature, it matures very late only at the end of November and provide a narrow window for the sowing of wheat in farmers’ filed. An experiment was conducted at Bihar Agricultural University, Sabour, Bihar during 2018 and 2019 to develop a semi-dwarf and early maturing lines derived from crossing of Katarni with 3 semi-dwarf high yielding cultivars and were advanced to F5 generation. In this study, 54 derived lines of Katarni in F6 generation were studied on the basis of 14 morphological traits and yield stability was analysed in 4 environments. The environments were created by different sowing dates across two years (2018 and 2019) in a single location at Bihar Agricultural University, Sabour. Significant variability was found among the genotypes and four principal components (PC) identified, out of which two contributed 98.9% of total variation. Six advanced breeding entries were found to be significantly superior over parental checks for grain yield. Five Katarni derived were identified as highly stable genotypes on the basis of GGE and AMMI stability analysis. All four environments were constituted in two mega environments in which first one shared the best set of Katarni-derived lines. The promising advanced breeding lines with higher yield and stable performance can further be evaluated under multi-location testing for varietal release.